Pengaruh Pengalaman Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Air Mineral Ds. Lesong Daya Kec. Batu Marmar Kab. Pamekasan - Agus Irawan; Budi Wahono; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2021)
AbstractGood performance will produce maximum results so that the work performance will be produced by employees in accordance with their portion in the company. Work experience and work motivation are believed to be able to influence employee performance to provide predetermined goals. With experience and motivation, performance will give higher results.Based on the results of this study it is proven that: simultaneously work experience and work motivation have a positive and significant effect on the performance of Air Mineral Al Hasany employees, work experience partially has a positive and significant effect on the performance of Air Mineral Al Hasany employees and work motivation partially has a positive and significant effect. on the performance of Al Hasany Mineral Water employees. These two variables are the most dominant work experience in influencing performance. Keywords: Work Experience, Work Motivation, Employee Performance